Synthetic gametes and the non-identity problem: the babies of tomorrow - Villalba, Adrian; Räsänen, Joona (Elsevier, 2026)
Synthetic DNA technologies may eventually enable the creation of synthetic gametes, which would offer precise control over genetic inheritance. This possibility raises profound ethical questions about human identity, genetic selection, and evolutionary boundaries. While synthetic gametes sidestep person-affecting ethical concerns, they present challenges for balancing reproductive autonomy and minimizing heritable disease, prompting interdisciplinary reflection.